Sustainable agriculture: developing a conceptual model for technology transfer - Boranbayeva, Ainur K. (2019)
Agriculture is the world’s largest industry. It is not only crucial for the well-being of the world population but also for most citizens whose prosperity is closely connected with the level of development in the agriculture industry. However, agriculture often places significant pressure on natural resources and the environment. According to the Food and Agriculture Organization, we pay an intolerable price in social and ecological terms to provide food for 7.5 billion people in the world. To be sustainable, while increasing the productivity, agriculture needs to preserve the environment and improve the social conditions of the population. The transfer of existing technology, for example, from developed countries, as well as new technology from research and development centers, can help in achieving the right balance in essential dimensions for sustainable agriculture. Building upon technology transfer models at the international level developed for the construction and the petroleum industries, we propose first a set of factors. Then, for each factor, while scrutinizing other technology transfer models at the inter-firm level, relevant sub factors were selected. The result is a conceptual model for technology transfer to be applied in the agriculture sector under a sustainable perspective.